Variáveis sociodemográficas e clínicas associadas ao apoio social percebido por pessoas com doenças renal crônica em hemodiálise - Saraiva, Santiago Marinheiro (2016)
Chronic kidney disease (CKD) requiring dialysis is associated with various stressors that negatively affect the dynamics of social relations. Social support received by people with CKD on dialysis directly influences the mortality and quality of life. In this context it is important to know the possible associations between social support offered to people with CKD on dialysis and sociodemographic and clinical variables. Our study aimed to verify the association of self-perceived social support with sociodemographic and clinical variables among people with CKD undergoing hemodialysis (HD). We included 161 patients with CKD undergoing HD from the only two existing dialysis centers in the north of the State of Ceará. Patients under the age of 18 years and time on HD less than three months were excluded. We used The Medical Outcomes Study Social Support Survey for evaluation of social support perceived by the participants. This instrument consists of 19 items covering five dimensions of social support: Material (provision of material assistance), Affective (physical displays of affection), Emotional (emotional needs), Information (count on people to inform and guide) and Positive Social Interaction (count with people to relax). The score generated by the instrument ranges from 0 (worst possible social support) to 100 (best possible social support). The following sociodemographic data were obtained: gender, age, religion and marital status. The socioeconomic classification corresponded to the criteria Brazil according to the Brazilian Association of Market Research Institutes, which results in the classification of five social classes: A (highest level) to E (lowest level). The following clinical data were obtained: etiology of CKD, time on maintenance HD and degree of comorbidities, according to Khan Index which ranks three degrees of comorbidity: grade I (low risk), grade II (medium risk) and grade III (high risk). Scores for each dimension of self-perceived social support were compared according to the following sociodemographic variables: men vs. women; elderly (older than or equal to 60 years) vs. non-elderly (age less than 60 years); married vs. not married; catholic vs. non-catholic; socioeconomic classes B + C vs. D + E. Scores for each dimension of self-perceived social support were compared according to the following clinical variables: time on maintenance HD up to 36 months vs. longer than 36 months; diabetics vs. non-diabetics; and low risk of comorbidity vs. medium + high risks. Student’s t test was used to infer the statistical significance of the comparisons. The p <0.05 was set to indicate statistical significance. The sample was formed by a majority of men (65.3%) with mean age of 50.3 years, with a greater concentration on socioeconomic classes C and D (91.3%) and a majority of catholics (79.5%). The main cause of CKD was hypertension (34.2%) followed by glomerulonephritis (25.2%) and diabetes mellitus (21.7%). People were treated by HD for 46.2 months on average. More than half the sample (50.9%) had low risk due to comorbidity. The Affective dimension of social support was the best scored (mean score=87.7 points) and the Positive Social Interaction was the worst score (mean score=73.5). The sociodemographic variables associated with social support were age, marital status, and socioeconomic status, as follows: elderly had higher scores for the dimension Material (91.6 vs. 80.5; p=0.005); married people perceived greater social support related to the dimensions Material and Emotional, respectively 86.7 versus 76.8 (p=0.015) and 86.4 versus 76.0 (p=0.008); and people from socioeconomic classes B and C scored more than the classes D and E in relation to the dimension Affective of social support (90.2 vs. 81.5; p=0.047). Among the clinical variables studied, the only variable associated with social support was time on HD, as follows: people with less time on HD perceived greater social support related to the dimension Material than people with more time on HD (86.8 vs. 77.2; p=0.040). The following persons in HD should be seen as at risk of receiving less social support: the younger, not married, from lower socioeconomic class and those on HD for more than 36 months. We propose the following strategies focused on people at risk of receiving less social support: educational interventions, search for material resources in the communities where people on HD live and strengthening the interaction of patients with family and friends